The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/2318-0331.0117160035
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal distribution of extreme pressures in a hydraulic jump downstream of a stepped spillway

Abstract: The overflow system of a dam safely controls the water level of a reservoir. The design of these structures should predict the damage caused by the action of the turbulent flow to which they are subject to. The combination formed by a stepped spillway followed by a stilling basin promotes a considerable portion of the energy dissipation in the actual chute of the stepped spillway but it is not sufficient to completely avoid the risk of damaging the basin. In this paper, we analyze the longitudinal distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…To analyze the effect of possible errors of measurement of extreme pressures commonly adopted in projects (P 0.1% and P 99.9% ), due to the uncertainties in the position of the transducer in the steps, experimental data of pressure measured with transducers by Sanagiotto & Marques (2008) were used in this study. The standard deviation values (σ d ) and statistical probability distribution coefficients N 0.1% and N 99.9% were calculated, respectively, using Equations 11 and 12, following the same methodology used in studies of extreme pressures in hydraulic jumps (Novakoski et al, 2017b;Teixeira, 2008…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the effect of possible errors of measurement of extreme pressures commonly adopted in projects (P 0.1% and P 99.9% ), due to the uncertainties in the position of the transducer in the steps, experimental data of pressure measured with transducers by Sanagiotto & Marques (2008) were used in this study. The standard deviation values (σ d ) and statistical probability distribution coefficients N 0.1% and N 99.9% were calculated, respectively, using Equations 11 and 12, following the same methodology used in studies of extreme pressures in hydraulic jumps (Novakoski et al, 2017b;Teixeira, 2008…”
Section: Discussionmentioning
confidence: 99%
“…The physical hydraulic structure used in this work is described in Sanagiotto (2003), Sanagiotto & Marques (2008) and Gomes (2006) and is very similar to the structure used in other studies (Conterato, 2011(Conterato, , 2014Conterato et al, 2015;Novakoski et al, 2017aNovakoski et al, , 2017bOsmar et al, 2018), with small differences in the approach channel and the channel downstream of the steps.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that maximum pressure fluctuations were identified at the center of the vertical curve and assume values of 1% of the flow kinetic energy at the terminal tangency point of the curve. Novakoski et al [30] investigated extreme pressures with different probabilities (P* k% ) on a smooth basin downstream of a stepped spillway. The results showed that the values of P* 0.1% and P* 99.9% have lower and higher values than the values observed downstream of the smooth chute, in the region near the spillway toe, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Farhoudi et al [19] studied the pressure fluctuations around some chute blocks in a St. Anthony Fall (SAF) type dissipation basin. Novakoski et al [20] showed that the negative pressures in the zone near the spillway toe represent the risk of cavitation in the dissipation basin. They concluded that the extreme pressures with the probabilities of occurrence equal to 0.1% and 1% require careful assessment.…”
Section: Introductionmentioning
confidence: 99%